Selecting the Best Alternative for Procurement of Equipment Labeling Facilities at PT XYZ Using the DELPHI and AHP Methods - Gilang Pratama; A. A. Bgs. Dinariyana Dwi Putranta (Global Writing Academica Researching and Publishing, 2025)
PT XYZ is a company that manages the Balikpapan Refinery Development Master Plan (RDMP) Project. This project aims to increase the refinery processing capacity and produce products with EURO V quality that are more environmentally friendly. Currently, the project is in the final construction phase, which will be followed by the commissioning phase, a phase that greatly requires effective equipment identification. In this project, the labels available on the equipment are not operationally adequate, and the procurement of facilities for equipment labeling is not included in the project's scope of work. There are three alternatives to solve this problem: implementing a change order in the project contract, implementing a label procurement framework contract, and procuring facilities independently by the relevant department. This study aims to choose the best procurement method among the three alternatives. Based on the questionnaire data filled out by respondents and processed using the Delphi analysis method, four criteria and twelve sub-criteria were obtained. These criteria were then processed using the AHP method to produce criteria weighting, namely cost (0.404), time (0.332), quality (0.164), and operational (0.100). Based on these criteria and sub-criteria, the best alternative for procurement of equipment labeling facilities at PT XYZ is independent facility procurement by the relevant department (0.454), followed by the implementation of label procurement framework contract (0.320), and the implementation of change orders on project contracts (0.226).